ГЛОБАЛИЗАЦИЯ ЭКОНОМИКИ И ЕЕ ВЛИЯНИЕ НА СТРУКТУРУ НАЛОГОВОЙ СИСТЕМЫ И НАЛОГОВОГО МЕХАНИЗМА (Journal of Economic Research & Business Administration, 2015)
Positive and negative influences of globalization processes on tax policy of the state are considered in article. Also problems of developing the tax policy in conditions of regionalization and integration are discussed.